Impact Assessment of The Covid-19 Pandemic on Service Performance of Sofia Airport - Nikolova, Christina; Garkova, Veronika (European Journal of Sustainable Development, 2022)
The main objective of the research presented in the paper is to examine the impact of the COVID pandemic on the volume of passenger and freight traffic and the quality of the services provided by Sofia Airport, as well as to examine the factors influencing the demand for air freight transport and the extent of their impact. The authors focus on using two approaches, namely SERVPERF and SERVQUAL, in studying factors influencing the demand for transport. The study analyses a system of indicators with independent influences on the demand for air transport, but they are all related to the development of macroeconomic indicators at the national level under the influence of the COVID pandemic. The study of the impact of the pandemic on the service performance and quality of services provided by Sofia Airport allows us to predict the volume of transport activity and to plan the activities of airlines and ground operators, their transport capacity, as well as the need for adopting measures for recovery of the airport from the negative impacts of the pandemic and the necessary investments in airport facilities. The authors argue that evaluating the service performance and the quality of services could contribute to developing appropriate measures for recovery. They summarized appropriate measures based on the leading quality indicators for air transport services. Keywords: Air Transport, Impact Assessment, COVID pandemic, Service Performance, Service Quality.